Border migrants and COVID-19: the right to access health services on the Brazil-Argentina-Paraguay triple border (Research, Society and Development, 2022)
Objective: to discuss the difficulties in accessing health care for immigrants in border regions, especially in the period of the COVID-19 pandemic. Methodology: this is a documentary research, of the narrative review type, for which it is not necessary to use explicit and systematic criteria for the search and critical analysis of the literature, however we emphasize that the searches were carried out in national journals, with publications in Portuguese, full and free access, without limitation of publication time. In order to have a broad search for studies, the gray literature was also used, for expanding the findings and reducing possible gaps on the subject. Results: the text discusses the bureaucratic processes of Brazilian migrants who live in Argentina and Paraguay and find it difficult to access health services in Brazil, especially during the COVID-19 pandemic. Conclusion: although the discussions regarding the recognition of the differences in the health systems of the different border countries, in terms of management and financing, as well as the degree of coverage, extension of programs, quality of care and the installed network itself, manifest themselves if a major obstacle guarantees health protection to the inhabitants of the border area, regardless of their nationality, and in atypical situations, such as COVID-19, this population is not considered in decision-making.